2015
DOI: 10.17265/1934-7391/2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility of Listeria spp. in Dairy Food Products and Water Samples in Dhaka, Bangladesh

Abstract: A total of 57 samples, of which 17 were surface water samples and 40 were dairy food samples (raw milk, pasteurized milk, icecream, sweet, milk based drink like matha and borhani) were tested for the isolation of Listeria spp. Putative Listeria isolates were identified by conventional microbiological tests and Analytical Profile Index. Overall prevalence of Listeria spp. in both food and water samples were 8.77%, of which one was (1.75%) Listeria monocytogenes, 2 (3.5%) were Listeria innocua and 2 were (3.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…were not detected from pasteurized milk. Similar results were reported by VardarÜnlü et al, (1998) and Sarker and Ahmed (2015). In contrast to our findings, Silva et al, (2003) detected Listeria spp.…”
Section: Discussionsupporting
confidence: 90%
“…were not detected from pasteurized milk. Similar results were reported by VardarÜnlü et al, (1998) and Sarker and Ahmed (2015). In contrast to our findings, Silva et al, (2003) detected Listeria spp.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical and food isolates have relatively low resistance to E (less than 3%) (Baquero et al., 2020 ). Both previous studies and the current study found the resistance of Listeria species to E to be higher than 3% (Akrami‐Mohajeri et al., 2018 ; Rahimi et al., 2010 , 2012 ; Sarker & Ahmed, 2015 ; Sołtysiuk et al., 2022 ). Antimicrobial resistant genes (ARGs) are typically encoded on mobile genetic elements (White et al., 2002 ).…”
Section: Discussionsupporting
confidence: 56%
“…Many raw and processed foods such as unpasteurized milk, soft cheeses, dairy products, red meats, poultry, sea foods, vegetables, fruits, sausages, smoked fish, salads, deli meat, and refrigerated ready-to-eat (RTE) foods have been identified for their risk of listeriosis (Valimaa et al, 2015). Of these foods, milk and other dairy products especially raw and soft cheeses have been implicated in about half of all the listeriosis outbreaks (Sarker & Ahmed, 2015;Komora et al, 2020). Biocontrol assays have received renewed attention in recent years as a possible antibiotic alternative to eliminate or control foodborne pathogens infections.…”
Section: Introductionmentioning
confidence: 99%